"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires